Deliberating Upon the Living Wage to Alleviate In-Work Poverty: A Rhetorical Inquiry Into Key Stakeholder Accounts - Hodgetts, Darrin J.; Young-Hauser, Amanda Maria; Arrowsmith, Jim; Parker, Jane; Carr, Stuart Colin; Haar, Jarrod; Alefaio, Siautu (Frontiers in Psychology, 2022)
Most developed nations have a statutory minimum wage set at levels insufficient to alleviate poverty. Increased calls for a living wage have generated considerable public controversy. This article draws on 25 interviews and four focus groups with employers, low-pay industry representatives, representatives of chambers of commerce, pay consultants, and unions. The core focus is on stakeholder use of prominent tropes for the living wage and against the living wage. We document how these tropes are drawn upon by participants with opposing positions using various rhetorical devices to craft their own rhetorical positions on the issue.